Effectiveness of miltefosine-pentoxifylline compared to miltefosine in the treatment of cutaneous leishmaniasis in C57Bl / 6 mice - Santarem, Ana Angélica Amorim (2014)
Introduction The treatment of leishmaniasis ischallenging, given the difficulties in drug administration and resistance. Therefore, we chose to test the efficacy of miltefosine combined with pentoxifylline. Methods Twenty-seven isogenic C57Bl/6 mice were infected with Leishmania (Leishmania) amazonensis, and equally divided into three groups: miltefosine (200mg/kg/day), miltefosine (200mg/kg/day) with pentoxifylline (8mg/kg/day), and untreated. Response to treatment was evaluated using paw diameter and parasitological criteria. Results The number of viable Leishmania reduced significantly within the miltefosine-pentoxifylline group (p < 0.05). Conclusions There is hope that a viable treatment exists for Leishmania infection.